Effect of Common Pavements on Interjoint Coordination of Walking with and without Robotic Exoskeleton. (1st October 2019) - Wang, Jinlei; Qiu, Jing; Hou, Lei; Zheng, Xiaojuan; Yu, Suihuai
Abstract : Background . The analysis and comprehension of the coordination control of a human gait on common grounds benefit the development of robotic exoskeleton for motor recovery. Objective . This study investigated whether the common grounds effect the interjoint coordination of healthy participants with/without exoskeletons in walking. Methods . The knee-ankle coordination and hip-knee coordination of 8 healthy participants in a sagittal plane were measured on five kinds of pavements (tiled, carpet, wooden, concrete, and pebbled) with/without exoskeletons, using the continuous relative phase (CRP). The root mean square of CRP (CRPRMS ) over each phase of the gait cycle is used to analyze the magnitude of dephasing between joints, and the standard deviation of CRP (CRPSD ) in the full gait cycle is used to assess the variability of coordination patterns between joints. Results . The CRPHip-Knee/RMS of the carpet pavement with exoskeleton is different from that of other pavements (except the tiled pavement) in the midstance phase. The CRPHip-Knee/RMS on the pebble pavement without exoskeleton is less than that on the other pavements in all phases. The CRPHip-Knee/SD of the pebble pavement without exoskeleton is smaller than that of other pavements. The CRPKnee-Ankle/SD with/without exoskeleton is similar across all pavements. Conclusion . The compressive capacity of the pavement and the unevenness of the pavement are important factors that influence interjoint coordination, which can be used as key control elements of gait to adapt different pavements for robotic exoskeleton. Novelty . We provide a basis of parameter change of kinematics on different common grounds for the design and optimization of robotic exoskeleton for motor recovery.